KESANTUNAN BERBAHASA PADA PERIBAHASA INDONESIA BERMAKNA SINDIRAN: KAJIAN PRAGMATIK - Nisa, Hilda Khoirun; Uswati, Tati Sri; Itaristanti, Itaristanti (HUMANIKA, 2020)
Immoral problems at the form of sarkasme which is identical with behavior insinuate in have leanguage, pushing research qualitative this to identify form proverb of Indonesian have a meaning of insinuation, to descirbe his context and meaning, and also obedient to describe of suavity principles hanve language at proverb of Indonesian have a meaning of insinuation. The target reached to pass method correct reading with descriptive approach qualitative. Source of data in this research refer at proverb dictionary in application of offline Fifth KBBI Edition and also dictionary print Proverb and Poetry Indonesia as other source. Proverb data have a meaning of insinuation mustered to pass documentation technique, continuation technique correct reading free entangle to speak, and technique note. Authenticity of data gathered data, to be strived with testing credibility through range of time in lengthening of peroeption, durability of fokus aa make up of assidinity, and triangulation of is source of data. Here in after analyse data done with technique link to conpare to equalize and link to compare to differentiate which is mustered in method correspond extralingual. This research yield proverb from have a meaning of insinuation pursuant to classification theory of majas marginally, among others form oposition of contradiction type, coherent of repetation type, retoris, and climax, and also comparison of supposing type of word, symbolic, and comparison of diction. Third of the form both of the same aim to the strengthen insinuation meaning in proverb. Besides, yielded also proverb meaning and context have a meaning of insinuation influenced by relation at the opposite of its of him which share to assist interpretation of used association. Context and the meaning constitute obediently of suavity principles have language of Leech at proverb of insinuation, proven of teared meaning which implied by figurative language, at the same time become marker of principal bowing to interest as elementary principle which obeyed by proverb of insinuation. Proven other obedient at humility principle, wise, and praise.